Plasmonic Chromatic Electrode with Low Resistivity. Issue 1 (December 2017) - Moon, Young; Do, Yun; Lee, Min; Hwang, Bo; Jeong, Dong; Ju, Byeong-Kwon; Choi, Kyung
Abstract We report on the optical and electrical properties of a novel plasmonic chromatic electrode (PCE). The PCE was composed of a metallic nano-hole array and ITO layer as a dielectric for electrical property. The structure design was optimized to obtain the matched condition between surface plasmon modes at the top and bottom metal-dielectric interfaces for high transmittance. The fabricated PCEs have high transmittance of 25 40% and low resistivity (level of 10−5 Ωcm) compared to conventional electrodes. Due to the multi-functionality and simple structure of PCEs, we predict the PCEs can be applied for advanced industrial use such as, high resolution, flexible, and stretchable devices.